Comparative assessment of SSAP, AFLP and SSR markers for evaluation of genetic diversity of durum wheat (triticum turgidum l. var. durum) - Mardi, M.; Naghavi, M. R.; Pirseyedi, S. M.; Alamooti, M. Kazemi; Monfared, S. Rashidi; Ahkami, A. H.; Omidbakhsh, M. A.; Alavi, N. S.; Shanjani, P. Salehi; Katsiotis, Andreas (My University, 2011)
Comparative assessment of genetic diversity of 122 durum wheat genotypes (Triticum turgidum L. var. durum) was performed using 73 SSAP polymorphic fragments, 123 AFLP polymorphic loci and 104 SSR alleles. SSAP and AFLP data showed a clear demarcation between the cultivars and landraces and SSR data classified cultivars and landraces according to their origin. Furthermore, the estimated genetic diversity of Iranian landraces was higher compared to the foreign entries and a loss of genetic diversity was observed from landraces to cultivars. This study determined that differences in genetic relationships revealed by SSAP, AFLP and SSR distances could not be attributed solely to differences in the level of polymorphism detected by each marker system. The molecular evidence of genetic diversity decrease of the durum wheat gene pool further strengthens the strategic relevance of undertaking appropriate genetic conservation measures for food security.
Keywords: AFLP; Durum; Genetic diversity; SSAP; SSR